ANALISIS PENGARUH DIMENSI PERILAKU KEPEMIMPINAN TERHADAP KEYAKINAN BAWAHAN (STUDI KASUS PADA BADAN PENGELOLA RSD DR. R. SOEDJATI KABUPATEN GROBOGAN - Rindyarini, Rindyarini; Titiek, Suwarti (Jurnal Ilmiah Telaah Manajemen, 2005)
This research in conducted to test model of syncretical leadership by Behling and Mc Fillen (1996) or can be told this research aim to test influence of display empathy, dramatized the mission, projects self-assurance-enhances the leaders image. assures follower belief by using analysis of multipl;e linier regression.Result of research show by partial and also by together displays emphaty, dramatizes the mission, project self - assurance, enhanches the leaders image., assures followers of their conpetency, provides opportunities for followers to experience succes have an significant effect to followers belief. Result of this study as according to result research by Behling and Mc Fillen (1996). Key words: displays empathy, dramatized the mission, project self-assurance, enhances the leaders image, assures followers of their competency, provides opportunities for followers to experience secces and follower belief.